2022
DOI: 10.3390/polym14193947
|View full text |Cite
|
Sign up to set email alerts
|

Structural Health Monitoring Impact Classification Method Based on Bayesian Neural Network

Abstract: This paper proposes a novel method for multi-class classification and uncertainty quantification of impact events on a flat composite plate with a structural health monitoring (SHM) system by using a Bayesian neural network (BNN). Most of the existing research in passive sensing has focused on deterministic approaches for impact detection and characterization. However, there are variability in impact location, angle and energy in real operational conditions which results in uncertainty in the diagnosis. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Novel AI-based methods for the inspection of the Automated Fiber Placement (AFP) process have also been presented by several researchers [139][140][141][142][143] . As part of health monitoring of structures, machine/deep learning models have been used for defect/damage detection [144][145][146][147][148][149][150] , characterization of cracks/delamination [151][152][153] and classification of impact levels 154 . Yu et al 154 demonstrated that probabilistic Bayesian and traditional artificial neural networks can successfully classify the energy levels of different impact events based on the signals obtained from a network of piezoelectric sensors.…”
Section: The Meta-verse Of Composites Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel AI-based methods for the inspection of the Automated Fiber Placement (AFP) process have also been presented by several researchers [139][140][141][142][143] . As part of health monitoring of structures, machine/deep learning models have been used for defect/damage detection [144][145][146][147][148][149][150] , characterization of cracks/delamination [151][152][153] and classification of impact levels 154 . Yu et al 154 demonstrated that probabilistic Bayesian and traditional artificial neural networks can successfully classify the energy levels of different impact events based on the signals obtained from a network of piezoelectric sensors.…”
Section: The Meta-verse Of Composites Manufacturingmentioning
confidence: 99%
“…As part of health monitoring of structures, machine/deep learning models have been used for defect/damage detection [144][145][146][147][148][149][150] , characterization of cracks/delamination [151][152][153] and classification of impact levels 154 . Yu et al 154 demonstrated that probabilistic Bayesian and traditional artificial neural networks can successfully classify the energy levels of different impact events based on the signals obtained from a network of piezoelectric sensors. Deep learning tools are particularly capable of such tasks when the signal is in the form of 2D/3D fields and maps 56,57 .…”
Section: The Meta-verse Of Composites Manufacturingmentioning
confidence: 99%
“…The first method extracts statistical features from time-series signals and uses them as the input to ML algorithm frameworks [ 28 , 29 , 30 ]. The second method utilizes the one-dimensional (1D) convolutional neural network (CNN) to automatically extract the features [ 31 , 32 , 33 , 34 ]. The 1DCNN has the same advantages as the CNN and is capable of learning more comprehensive features (i.e., less susceptible to subjective experience).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most NDT methods are time-consuming, expensive, require access in situ, and cannot apply continuous and real-time monitoring. Infrared thermography [ 30 , 31 ], ultrasonic C-scan detection, acoustic emission (AE), and resistance strain gauges [ 32 ] are commonly used to check the integrity of composite materials [ 33 , 34 , 35 ]. The latter is predominantly destined for static measurements and achieves low transverse sensitivity [ 36 ].…”
Section: Introductionmentioning
confidence: 99%